Pengaruh Etika Bisnis Islami Terhadap Kinerja Pembiayaan Mudharabah Melalui Informasi Asimetri Pada Bank Syariah di Jawa Timur - Roziq, Ahmad (JURNAL EKONOMI AKUNTANSI DAN MANAJEMEN, 2010)
Low level of performance of mudharaba financing is likely a multi-dimensional problems that have occurred since a long time and no inclination to change. Implications of the resultsof the high-profit and loss sharing (such as murabaha) is the formation of public perception that sharia banking is almost no difference with the conventional banking. Such perceptions will form a separate reputational risk that is feared will lead to cynicism among the public that sharia banking business is only a mindset change of name only, while the perpetrators are still common. State performance of sharia banking mudharaba financing portofolio at sharia banking is to show the discrepancy between theory and practical implementation of mudharaba financing. This study examines the effect of Islamic business ethics toward performance of mudharaba financing through information asymmetry. With the known variables than can affect the performance of mudharaba financing will be obtained by solving the solution of gap/inconsistencies between between theory and practical implementation of mudharaba financing and can answer the phenomenon of mudharaba financing is low performance. This study examines the effect of Islamic business ethics toward performance of mudharaba financing through information asymmetry. The study is based on agency theory and theory of sharia enterprise. Agency theory to explain the phenomenon of information asymmetry between the parties of mudharib and sharia bank. Sharia enterprise theory to explain the necessity of sharia Islamic ethics in running the business. These studies included in this type of survey research used for the purposes of clarification or confirmation, or also known as hypothesis testing research, which is intended to explain the influence between variable or causal relationship between variables by testing the hypothesis. The population of this study are all branches of sharia banks and sharia business unit which operate mudharaba financing in East Java, which amounts to 19 bank branches of sharia (sharia business units) with 35 respondents.Methods of data analysis in this study is Structural Equation Modeling using Partial Least Square (PLS) with the aid of computer programs SmartPLS package. The study results showed that Islamic business ethics significantly affect on information asymmetry and does not significantly affect to the performance of mudharabafinancing. Information asymmetry has a significant effect on the risk of mudharaba financing and the performance of mudharabafinancing. This study supports the agency theory and sharia enterprise theory which explains problems in achivement of the performance of mudharaba financing. The study suggests that problems in achivement of the performance of mudharaba financing should be explaned with sharia agency theory in accordance with the Quran as-Shaad verse 24 and the hadith narrated by Bukhari number 2079. Key words: mudharaba financing, Islamic business ethics, information asymmetry, performance Pemetaan Kualitas Laporan Keuangan Pemerintah Daerah di Kawasan Timur Jawa Timur Berbasis Sistem Informasi Geografi.